Overview of strategies to improve the antibacterial property of dental implants - Zhai, Shaobo; Tian, Ye; Shi, Xiaolu; Liu, Yang; You, Jiaqian; Yang, Zheng; Wu, Yuchuan; Chu, Shunli (Frontiers in Bioengineering and Biotechnology, 2023)
The increasing number of peri-implant diseases and the unsatisfactory results of conventional treatment are causing great concern to patients and medical staff. The effective removal of plaque which is one of the key causes of peri-implant disease from the surface of implants has become one of the main problems to be solved urgently in the field of peri-implant disease prevention and treatment. In recent years, with the advancement of materials science and pharmacology, a lot of research has been conducted to enhance the implant antimicrobial properties, including the addition of antimicrobial coatings on the implant surface, the adjustment of implant surface topography, and the development of new implant materials, and significant progress has been made in various aspects.Antimicrobial materials have shown promising applications in the prevention of peri-implant diseases, but meanwhile, there are some shortcomings, which leads to the lack of clinical widespread use of antimicrobial materials. This paper summarizes the research on antimicrobial materials applied to implants in recent years and presents an outlook on the future development.